The dental use by pediatric patients in the National Health Insurance of Taiwan in 2020 - Feng-Chou Cheng; Chun-Pin Chiang (Elsevier, 2022)
Background/Purpose: Although the penetration rate of National Health Insurance (NHI) of Taiwan is as high as 99%, our children still face the impact of oral diseases. This study investigated the profile of dental use by pediatric patients in the NHI of Taiwan in 2020. Materials and methods: Data on the population and medical records of NHI were obtained from the websites of Ministry of the Interior and the NHI Administration. The pediatric dental patient data were divided into 3 age groups (0-4, 5-9, and 10-14 years) to investigate and analyze dental treatment records claimed in 2020. Results: In Taiwan, the two most common oral diseases in children were dental caries and gingivitis & periodontal diseases. The dental use rate for treatment of dental caries in children was 16.84% for the 0-4-year, 55.69% for the 5-9-year, and 34.29% for the 10-14-year age groups. Moreover, in all 3 age groups of children, dental caries needed the highest NHI expenses, followed in a descending order by gingivitis & periodontal diseases and diseases of pulp & periapical tissues. Among them, dental caries needed more than half (51.15%) of all dental NHI expenses in the 5-9-year age group. Conclusion: Due to the long-term lack of awareness and behavior for oral health care among Taiwanese people, the dental caries rate of the children remains high. From a cost-effectiveness viewpoint, Taiwan government should develop a better oral health care policy to prevent dental caries and gingivitis & periodontal diseases in children.